Keep the colour in palm oil! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Unrefined oil derived from oil palm is red, rich in carotene and vitamin A, and has an acidic taste that is much appreciated bythose who use it. But it appears that for some time there has been reluctance to use palm oil with its natural colouring....